2020
DOI: 10.3390/app10207314
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization of a Passivity-Based Controller for Dynamic Positioning of Ships

Abstract: Dynamic positioning (DP) control system is an essential module used in offshore ships for accurate maneuvering and maintaining of ship’s position and heading (fixed location or pre-determined track) by means of thruster forces being generated by controllers. In this paper, an interconnection and damping assignment-passivity based control (IDA-PBC) controller is developed for DP of surface ships. The design of the IDA-PBC controller involves a dynamic extension utilizing the coordinate transformation which adds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Another category for meta-heuristic algorithms is inspired by physics, like the gravitational search algorithm [42]. Other meta-heuristic algorithms category is swarm-based, like Fish Search Optimization FSO and particle swarm optimization PSO [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another category for meta-heuristic algorithms is inspired by physics, like the gravitational search algorithm [42]. Other meta-heuristic algorithms category is swarm-based, like Fish Search Optimization FSO and particle swarm optimization PSO [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulation results showed that the proposed method could eliminate body frame errors compared with traditional methods. In [12], Ryalat et al proposed an Interconnection and Damping Assignment-Passivity-Based Control (IAD-PBC) controller and used PSO to obtain the gains of the IDA-PBC controller which provides an effective way to tune these gains, thus improving the control performance of DP system. The simulation showed that the states with PSO converged to the desired position and heading angle and had less overshooting.…”
Section: Intelligent Algorithmmentioning
confidence: 99%
“…e end-to-end network delay will increase, which will also lead to a decline in link utilization, a sharp drop in throughput, and even paralysis of the entire network system. In recent years, more and more scholars have begun to pay attention to and start to study the problem of network congestion, hoping to find ways and means to effectively solve such problems [14][15][16][17].…”
Section: Related Workmentioning
confidence: 99%